2009
DOI: 10.1007/s00381-009-0993-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of spinal abnormalities in patients with spastic diplegia 17 to 26 years after selective dorsal rhizotomy

Abstract: Except for spondylolisthesis, spinal deformities did appear to progress with time. However, this increase was not marked, and the development of relatively mild scoliosis was the only statistically significant increase. This group of patients requires continued follow-up. Further studies are required to ascertain the natural history of spinal deformity in adults with spastic diplegia who have not had SDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 36 publications
3
61
1
2
Order By: Relevance
“…A substantial number of participants exhibited weakness, with most apparent impairments in gluteus muscles and hamstrings, possibly contributing to the crouched gait pattern as described for the participants in the SDR group. In addition, impaired hip abductor strength was also observed 17 years after SDR [14], which is in line with the lack of hip abduction in late stance as reported in our SDR group.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A substantial number of participants exhibited weakness, with most apparent impairments in gluteus muscles and hamstrings, possibly contributing to the crouched gait pattern as described for the participants in the SDR group. In addition, impaired hip abductor strength was also observed 17 years after SDR [14], which is in line with the lack of hip abduction in late stance as reported in our SDR group.…”
Section: Discussionsupporting
confidence: 90%
“…The influence of SDR on muscle strength is debatable, and varying outcomes ranging from deterioration, unchanged, or improvements in strength during the first years after surgery, have been reported [6,8]. Unfortunately, no pre-operative muscle strength assessment data was available for the current SDR group, but we do have information about muscle strength more than 17 years after SDR [14]. A substantial number of participants exhibited weakness, with most apparent impairments in gluteus muscles and hamstrings, possibly contributing to the crouched gait pattern as described for the participants in the SDR group.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The long-term review of patients revealed a high incidence of minor scoliotic curves at a minimum of 17 years post-rhizotomy [30]. Generally, there is a relationship between the severity of involvement and the incidence of scoliosis [31,32].…”
Section: Disadvantages Of Selective Dorsal Rhizotomymentioning
confidence: 99%